Inclusive search for new physics with like-sign dilepton events in pp̄ collisions at s=1.96TeV - Abulencia, A; Adelman, J; Affolder, T; Akimoto, T; Albrow, MG; Ambrose, D; Amerio, S; Amidei, D; Anastassov, A; Anikeev, K; Annovi, A; Antos, J; et al. (2007)
We describe a search for anomalous production of events with two leptons (e or μ) of the same electric charge in pp̄ collisions at a center-of-mass energy of 1.96 TeV. Many extensions to the standard model predict the production of two leptons of the same electric charge. This search has a significant increase in sensitivity compared to earlier searches. Using a data sample corresponding to 1fb-1 of integrated luminosity recorded by the CDF II detector, we observe no significant excess in an inclusive selection (expect 33.2±4.7 events, observe 44) or in a supersymmetry-optimized selection (expect 7.8±1.1 events, observe 13.) © 2007 The American Physical Society.